2021
DOI: 10.3390/jrfm14080359
|View full text |Cite
|
Sign up to set email alerts
|

Managing Risks in the Improved Model of Rolling Mill Loading: A Case Study

Abstract: This article reflects the main sources of risks for metallurgical enterprises in Russia, presenting the implementation of an innovative approach to increasing the competitiveness of an industrial enterprise, which is a typical representative of large enterprises of the metallurgical industry, based on the development of risk-oriented thinking when loading rolling mills with orders of intersecting assortment according to a new model. To reduce the emerging risks of a new model of the loading process of rolling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The study conducted shows that they are a risk in managing the department in higher education. This is in line with the research finding stating that higher education faces some organizational risks, from political and reputational risks, financial and economic risks, socio-psychological risks, and organizational or management risks (Deineha et al, 2020); (Perera et al, 2020); (Syreyshchikova et al, 2021). The need to understand the risk for department managers becomes an essential thing (Susanti, Sumiyati, & Tritjahjono, 2020).…”
Section: Quality Of Higher Education Graduates In Risk Managementsupporting
confidence: 76%
“…The study conducted shows that they are a risk in managing the department in higher education. This is in line with the research finding stating that higher education faces some organizational risks, from political and reputational risks, financial and economic risks, socio-psychological risks, and organizational or management risks (Deineha et al, 2020); (Perera et al, 2020); (Syreyshchikova et al, 2021). The need to understand the risk for department managers becomes an essential thing (Susanti, Sumiyati, & Tritjahjono, 2020).…”
Section: Quality Of Higher Education Graduates In Risk Managementsupporting
confidence: 76%
“…Figure 2 shows the possible causes of waste, including shop floor waste and environmental waste, found in a comprehensive literature review. The previous researchers argued that waste directly impacts worker performances, whether it is related to the environment or the shop floor [59,60]. Furthermore, they demonstrated that environmental waste results in inconvenient operational conditions and shop floor waste results in higher lead time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 8 shows the actions taken to improve the shop floor, while Table 9 shows the list of requirements for the different processes of the shop floor. By inspecting the production on the shop floor and analyzing the information gathered from many sources, it was found that some of the activities and processes involved in production are the cause of high PT, which need to be eliminated [47][48][49][50][51]. Table 8 shows the actions taken to improve the shop floor, while Table 9 shows the list of requirements for the different processes of the shop floor.…”
Section: Resultsmentioning
confidence: 99%